2018
DOI: 10.31219/osf.io/dsx6y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequency Effects on Memory: A Resource-Limited Theory

Abstract: We present a review of frequency effects in memory, accompanied by a theory of memory, according to which the storage of new information in long-term memory (LTM) depletes a limited pool of working memory (WM) resources as an inverse function of item strength. We support the theory by showing that items with stronger representations in LTM (e.g. high frequency items) are easier to store, bind to context, and bind to one another; that WM resources are involved in storage and retrieval from LTM; that WM capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 163 publications
(366 reference statements)
0
17
0
Order By: Relevance
“…The ability to form long-term associative memories also depends on working memory (WM) capacity (Marevic, Arnold, & Rummel, 2018; Unsworth & Spillers, 2010). To explain results like these, we have proposed that binding in memory depletes a limited WM resource that recovers over time (Popov & Reder, in press; Reder, Liu, Keinath, & Popov, 2016; Reder, Paynter, Diana, Ngiam, & Dickison, 2007; Shen, Popov, Delahay, & Reder, 2018). According to this model, processing weaker items requires more resources than processing stronger items.…”
mentioning
confidence: 99%
“…The ability to form long-term associative memories also depends on working memory (WM) capacity (Marevic, Arnold, & Rummel, 2018; Unsworth & Spillers, 2010). To explain results like these, we have proposed that binding in memory depletes a limited WM resource that recovers over time (Popov & Reder, in press; Reder, Liu, Keinath, & Popov, 2016; Reder, Paynter, Diana, Ngiam, & Dickison, 2007; Shen, Popov, Delahay, & Reder, 2018). According to this model, processing weaker items requires more resources than processing stronger items.…”
mentioning
confidence: 99%
“…However, it is reasonable to infer that the experience of significant pain is sufficiently distracting to impact participant's attention, leading to decreased memory for words immediately followed by (and thus paired with) a painful shock. Though performance on a working memory task was not directly examined in this study, engagement of working memory resources, necessary for successful encoding into long-term memory (Baddeley, 2010), can be reduced by other experimental events (Popov & Reder, 2018). A division of attention is consistent with a reduction in working memory resources available for encoding, specifically binding the word items to experimental context.…”
Section: Recognition Memory Performancementioning
confidence: 81%
“…One possibility is that while explicit beliefs about information value triggered the engagement of strategic control, stimulus familiarity (as indexed by repetition suppression (Gonsalves et al, 2005)) may have facilitated encoding of novel associations, even in the absence of controlled strategy use. Indeed, prior work suggests that stronger memory traces for constituent components enhances associative memory (Chalmers & Humphreys, 2003; Popov & Reder, 2020; Reder et al, 2016). However, in our previous behavioral work (Nussenbaum et al, 2020), we found that removing the relation between item frequency and reward value eliminated the memory benefit for associations involving high-frequency items, suggesting that stimulus familiarity itself did not account for the influence of item frequency on memory in our task.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately following encoding, we administered a memory test in which participants had to select each item’s correct associate. Because frequency of exposure to an item may facilitate subsequent associative memory even when it does not signal the value of information (Popov & Reder, 2020; Reder et al, 2016), in our prior behavioral study (Nussenbaum et al, 2020), we examined the effects of item frequency on subsequent associative memory in two contexts: one in which item frequency signaled information value and one in which it did not. Critically, we found that with our experimental design, frequency only facilitated memory when it signaled the value of remembering information — increased item exposure did not in and of itself enhance subsequent associative memory.…”
Section: Introductionmentioning
confidence: 99%